2019
DOI: 10.3389/fendo.2019.00295
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Analysis Toward Different Glucose Tolerance-Related Gut Microbiota and Diet

Abstract: Objective: There is evidence that type 2 diabetes (T2DM) is affected by gut microbiota, and gut microbiota diversity modified by diet. To investigate its modifications in Uyghur patients with different glucose tolerance, we enrolled 561 subjects: newly diagnosed T2DM ( n = 145), impaired glucose regulation (IGR) patients ( n = 138) and in normal control (NC) population ( n = 278). Methods: The nutrient intak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(74 citation statements)
references
References 47 publications
4
66
1
Order By: Relevance
“…Similar phenomena have been found in previous studies on sika deer [29] and human living environment [48] --different living environment makes spirochaetae only appear in intestinal ora of a certain living environment. In addition, studies have shown that animals fed diets rich in fungi, vitamin C and dietary ber have lower levels of spirochaetae in gut microbiota [49], which is in line with our experimental animal Siberian musk deer similar, but need further validation.…”
Section: Discussionsupporting
confidence: 86%
“…Similar phenomena have been found in previous studies on sika deer [29] and human living environment [48] --different living environment makes spirochaetae only appear in intestinal ora of a certain living environment. In addition, studies have shown that animals fed diets rich in fungi, vitamin C and dietary ber have lower levels of spirochaetae in gut microbiota [49], which is in line with our experimental animal Siberian musk deer similar, but need further validation.…”
Section: Discussionsupporting
confidence: 86%
“…Similar phenomena have been found in previous studies on sika deer [30] and human living environment [48] --different living environment makes spirochaetae only appear in intestinal ora of a certain living environment. In addition, studies have shown that animals fed diets rich in fungi, vitamin C and dietary ber have lower levels of spirochaetae in gut microbiota [49], which is in line with our experimental animal Siberian musk deer similar, but need further validation.…”
Section: Discussionsupporting
confidence: 86%
“…The proportions of short chain fatty acids (SCFAs) produced increase with the number of Fibrobacteres 59 . Spirochaetae and Actinobacteria produce several enzymes that break down plant biomass into simple sugars or fatty acids 60,61 . Nevertheless, these phyla had only minor impacts on the total VFA level in the rumen fluid as their total abundance for both treatment groups was < 1.6%.…”
Section: Discussionmentioning
confidence: 99%